Kajian Tentang Tarif Pelayanan Jasa Kargo dan Pos Pesawat Udara di Bandara Sam Ratulangi Manado - Dina Yuliana; Eny Yuliawati (Research and Development Agency of The Ministry of Transportation, 2009)
Research about Cargo and Post Service Charge in Sam Ratulangi Airport has been done. The result show that Cargo and Post Service Charge based fare(Rp.515,- per kg) and cargo companys willingness to pay (Rp.323,- per kg) are higher than current cargo and post service charge (Rp.300,- per kg) and based on their perception it was proved that almost 53,3% stated good 46,7% fair and there is no client stated bad against the facility of Cargo and Post Service Charge outgoing domestic.